Mutagenic Effects of Ethyl Methanesulfonate on Morphological and Growth Characteristics of Neolamarckia cadamba Plantlets - Wei Seng, Ho; Delvino, D. Dalin; Kwong Hung, Ling (Science Alert, 2022)
Background and Objective: Neolamarckia cadamba (Roxb.) Bosser is an economically important timber species used for light construction due to its light hardwood characteristic. Ethyl methanesulfonate (EMS) is a widely used chemical mutagen in plants as it gives a high frequency of point mutations. Hence, this study aimed to determine the lethal concentration 50 (LC50) of EMS and the mutagenic effects of EMS on growth characteristics and morphological variations of N. cadamba derived from nodal explants. Materials and Methods: Seeds derived from the candidate plus tree N5 were germinated in vitro. The nodal explants excised from the plantlets were used as the material for in vitro mutagenesis with different concentrations of EMS (0.1, 0.3, 0.6 and 1%) and durations (1, 2, 3 and 4 hrs). Results: The findings showed that the survival percentage was significantly reduced as both EMS concentration and treatment duration increased. The LC50 was 1.3% for 2 hrs, 0.4% for 3 hrs and 0.3% for 4 hrs. Various responses were observed in the EMS-treated explants. These include reduced and slower shoot induction, reduced number of shoot formations, reduced callus formation and lower plant height. Morphological abnormalities were also identified among the survived explants, such as unifoliate orbicular leaves, pointy leaves, small apical leaves, stunted shoot growth and distorted shoot formation. Conclusion: The present findings show that nodal explants can be used for in vitro EMS mutagenesis besides seeds as the most widely used material for mutation study. The putative mutants derived from this study could be used for future breeding and genomics research of N. cadamba.